SOME ISSUES OF SOCIO-POLITICAL PROCESSES IN KHOREZM IN THE FIRST HALF OF THE 20S OF THE 20TH CENTURY (TAMADDUN NURI JURNALI, 2025)
This article analyzes the national-territorial demarcation processes carried out in Central Asia in the 20s-30s of the 20th century. In particular, in the first half of the 20s of the 20th century, there are comments on the socio-political changes that took place in the Khorezm oasis in connection with the political company of the Soviet government.